Analysis of Mathematic Representation Ability of Informatics Engineering Students in Assignment Problems - niska shofia; Siti Rochana; Suryo Widodo (MEJ (Mathematics Education Journal), 2020)
Mathematics is a field of science that can improve a person's ability to think logically, critically, rationalistically, effectively, carefully and efficiently. To find out a person's ability to think logically, critically, rationalistically, effectively, carefully and efficiently in solving mathematical problems, an analysis of mathematical representations is needed. Mathematical representation is needed in solving Operations Research problems, because operations research uses a mathematical model as a problem-solving approach. This research discusses the mathematical representation ability of informatics engineering students at Nusantara University PGRI Kediri in solving assignment problems in Operations Research courses. The research method used includes descriptive research with a qualitative research approach. Data were taken directly from the research location using interviews and tests on 3 research subjects, namely students with high, medium and low abilities. The subject selection is based on the results of the dialogue between the researcher and the student's mathematics subject lecturer. Based on the results of research, high-ability students can complete multiple representations both visually, symbolically and verbally. Likewise for the mathematical representation of moderate-capable students is having multiple representations, but there are steps in solving that are missed in verbal representations. Low-ability students only provide visual and verbal representations, while symbolic representations still have errors. However, all three are still lacking in terms of the implementation of the final results